Legal Review of Local Wisdom of Indigenous Communities of Siak District in the Management of Slum Housing and Slum Settlement Locations - Evi Deliana; Nurahim Rasudin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
Law Number 1 of 2011 in Article 98 paragraph (3) concerning Housing and Settlements, it is explained that the regional government has the authority to conduct arrangements and determine the location of slum housings and urban slums. This is what underlies the Regional Government of Siak Regency to have a role in identifying various local wisdoms in its region. The existence of the local wisdom of the indigenous people of Siak can be viewed from the legal aspect of structuring the location of housing and slums as mandated by legislation and implemented in the Letter Regent Decree Number 523/HK/KPTS/2014 concerning Determination of Slum and Slum Housing Locations in Siak Regency and Regent Decree Number 302/HK/KPTS/2017 concerning Slum and Slum Residential Housing Locations in Siak Regency. The result is the existence of the local wisdom of Indigenous people of Kampung Buatan II, Koto Ghasib Subdistrict did not work optimally, because it had not maximized the role of the Riau Malay Customary Institution in Siak Regency. However, the noble values of local wisdom in Malay indigenous communities in structuring the location of housing and slums are known from their ancestors expressed in a proverb or customary expression in preserving nature around us to create a clean, healthy life by understanding the meaning of development, understanding the ins and outs of religion and culture and the social norms of the people, so that development is truly beneficial for all levels of society.